Dampak Perbedaan Varietas Terhadap Morfofisiologis Kedelai Tercekam Kekeringan - Fahri, Romi; Kiuk, Yosni (JURNAL AGROPLASMA, 2025)
Soybean production in Indonesia has not shown a satisfactory trend, compounded by drought problems that adversely affect plant growth and metabolism. One of the various solutions offered is the use of drought-resistant/tolerant soybean varieties. This study aims to examine how drought-resistant/tolerant varieties differ from drought-susceptible varieties in their morphophysiological response to drought. The study was conducted in a plastic house in Aras Kabu Village, Beringin Subdistrict, Deli Serdang Regency, North Sumatra, using a randomised block design with two factors and three replicates. The first factor was soil moisture conditions, consisting of 80% field capacity (FC) and 40% FC. The second factor was the testing of the Grobogan and Dering varieties. The observation parameters consisted of the number of leaves and leaf K uptake. The results showed that there was a significant interaction between the use of varieties and drought conditions, where the Dering variety significantly reduced the number of leaves, while the Grobogan variety, which is susceptible to drought, increased leaf K uptake to survive. Keywords: soybean, drought, stress, varieties